2022
DOI: 10.3390/jmse10020237
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics, Transcriptional Response to Heat Shock, and Gut Microbiota of the Hong Kong Oyster Magallana hongkongensis

Abstract: The Hong Kong oyster Magallana hongkongensis, previously known as Crassostrea hongkongensis, is a true oyster species native to the estuarine-coast of the Pearl River Delta in southern China. The species—with scientific, ecological, cultural, and nutritional importance—has been farmed for hundreds of years. However, there is only limited information on its genetics, stress adaptation mechanisms, and gut microbiota, restricting the sustainable production and use of oyster resources. Here, we present population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…It has also been shown that the Hippo signaling pathway is considered to be an important pathway for temperature adaptation in honeybees (Chen et al, 2016;Chen et al, 2018;Shi et al, 2020). The Glutathione metabolism signaling pathway found in Magallana hongkongensis from Hong Kong Island responds to altered redox homeostasis induced by heat stress and is involved in mediating oxidative stress responses (Xie et al, 2022). This may be required for adaptation to tropical island environments, which provides a basis for our understanding of tropical island adaptation in A. cerana and provides a reference for subsequent improvement of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the Hippo signaling pathway is considered to be an important pathway for temperature adaptation in honeybees (Chen et al, 2016;Chen et al, 2018;Shi et al, 2020). The Glutathione metabolism signaling pathway found in Magallana hongkongensis from Hong Kong Island responds to altered redox homeostasis induced by heat stress and is involved in mediating oxidative stress responses (Xie et al, 2022). This may be required for adaptation to tropical island environments, which provides a basis for our understanding of tropical island adaptation in A. cerana and provides a reference for subsequent improvement of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the Hippo signaling pathway is considered to be an important pathway for temperature adaptation in honeybees (Chen et al, 2016 ;Chen et al, 2018 ;Shi et al, 2020). The Glutathione metabolism signaling pathway found inMagallana hongkongensis from Hong Kong Island responds to altered redox homeostasis induced by heat stress and is involved in mediating oxidative stress responses (Xie et al, 2022). This may be required for adaptation to tropical island environments, which provides a basis for our understanding of tropical island adaptation in A.cerana and provides a reference for subsequent improvement of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%